(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Modeling of oil and gas reservoirs on a computational platform requires a precise mathematical model of the system, which describes the fluid flow in porous media based on fundamental physical laws governing their movement within the reservoir. Currently, well-established mathematical models exist that describe the multiphase filtration processes of fluids in porous media. Using the filtration theory equations, this work derives a system of equations that describes the transient filtration processes of oil and gas in a reservoir. The model provides a theoretical basis for simulating complex multiphase flows, which are critical for optimizing reservoir management and production strategies.